Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

1. Which equation is true?

A. [tex]$\frac{5}{8}=-\left(\frac{-5}{-8}\right)$[/tex]

B. [tex]$\frac{-3}{-4}=-\frac{3}{4}$[/tex]

C. [tex]$-\left(\frac{12}{-17}\right)=\frac{12}{17}$[/tex]

D. [tex]$\frac{9}{-13}=-\left(\frac{-9}{13}\right)$[/tex]


Sagot :

Let's carefully analyze each of the equations to determine which one is true.

### Option A:
[tex]\[ \frac{5}{8} = -\left(\frac{-5}{-8}\right) \][/tex]

First, simplify the right side:
[tex]\[ \frac{-5}{-8} = \frac{5}{8} \][/tex]
Therefore, the equation becomes:
[tex]\[ \frac{5}{8} = -\left(\frac{5}{8}\right) \][/tex]
This simplifies to:
[tex]\[ \frac{5}{8} = -\frac{5}{8} \][/tex]
Clearly, this is false since a positive number is not equal to its negative.

### Option B:
[tex]\[ \frac{-3}{-4} = -\frac{3}{4} \][/tex]

First, simplify the left side:
[tex]\[ \frac{-3}{-4} = \frac{3}{4} \][/tex]
Therefore, the equation becomes:
[tex]\[ \frac{3}{4} = -\frac{3}{4} \][/tex]
This simplifies to:
[tex]\[ \frac{3}{4} = -\frac{3}{4} \][/tex]
Again, this is false since a positive number is not equal to its negative.

### Option C:
[tex]\[ -\left(\frac{12}{-17}\right) = \frac{12}{17} \][/tex]

First, simplify the expression inside the parentheses:
[tex]\[ \frac{12}{-17} = -\frac{12}{17} \][/tex]
So the equation becomes:
[tex]\[ -\left(-\frac{12}{17}\right) = \frac{12}{17} \][/tex]
Simplify further:
[tex]\[ \frac{12}{17} = \frac{12}{17} \][/tex]
This equation is true since both sides are equal.

### Option D:
[tex]\[ \frac{9}{-13} = -\left(\frac{-9}{13}\right) \][/tex]

First, simplify the right side:
[tex]\[ \frac{-9}{13} = -\frac{9}{13} \][/tex]
So the equation becomes:
[tex]\[ \frac{9}{-13} = \frac{9}{13} \][/tex]
This simplifies to:
[tex]\[ -\frac{9}{13} = \frac{9}{13} \][/tex]
This is false since a negative number is not equal to its positive counterpart.

After evaluating each equation, we find that the true statement is:

[tex]\[ -\left(\frac{12}{-17}\right) = \frac{12}{17} \][/tex]

Thus the correct answer is C.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.